Kepribadian Tokoh Utama dalam Novel Negeri Para Bedebah Karya Tere Liye Kajian Psikoanalisis Carl Gustav Jung - Renni Handayani Sembiring; Herlina Herlina; Siti Gomo Attas (TRANSFORMATIKA, 2018)
This study aimed at finding out the main characters’ personality in the novel of Negeri Para Bedebah by Tere Liye based on Carl Gustav Jung’s psychoanalysis. The research method used qualitative with content analysis. Data were collected by inventorying Thomas's conversation based on Carl Gustav Jung's psychoanalytic personality characteristic. It consists of think extrovert, feels extrovert, sense extrovert, intuition extrovert, think introvert, feel introvert, sensitive introvert, and intuition introvert. The results revealed that the discovery of eight main characters’ personality. First, think extrovert is demonstrated by the ability of intellectual analysis of objective experience. Second, feel extrovert is found by responding emotionally to objective reality. Third, sense extrovert is the tendency of figures to analyze the situation. Fourth, intuition extrovert is seen by its character does not care about logic. Fifth, think introvert figure depiction looks inflexible, cold, judge, and cruel. Sixth, feel introvert showed by figures are selfish and unsympathetic. Seventh, sense introvert found the ability of the senses to give them subjective meaning. Eighth, intuition introvert is demonstrated by the figure closing in and keeping the distance from the others. In conclusion, the eight personality types can be found on the whole structure of an irregular novel story.